ADVANCED TECHNOLOGIES OF ELECTRONIC EDUCATIONAL SYSTEMS DEVELOPMENT - Shishkina, M. (Journal of Information Technologies in Education (ITE), 2011)
Actual problems and contradictions of electronic educational systems development are described: availability of education, quality of educational services; individualization of education; exposures and advantages in using of computer technology; standardization of technologies and resources. Tendencies of their solution in the view of development of new advanced technologies of e-education are specified. The essence and advantages of using the cloud computing technologies as a new platform of distributed learning are specified. Advanced directions of cloud-based data usage in executive system of education are declared: access management, content management, asset management, communications management.